2022
DOI: 10.1101/2022.12.14.22283438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fastest may not maximize gait quality: differential and individual-specific immediate effects of gait speed on biomechanical variables post-stroke

Abstract: Background: A common perspective in post-stroke gait training is that walking at the fastest safe speed maximizes the quality of gait biomechanics, with limited detrimental effects on compensatory biomechanics and inter-limb asymmetry. This fastest is best perspective is highly relevant to treadmill training paradigms, as mass high-intensity stepping practice with high-quality biomechanics can improve walking function and reinforce desirable gait patterns. However, it is unclear if walking at the fastest safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, these systems still generate a lot of data, subject to interpretation, including multiple joint angles, and over 20-50 spatiotemporal gait metrics. 44 , 45 Thus, another avenue for future research is the development and clinical validation of gait analysis methods that can be applied to clinical settings, while being rapid, objective, intuitive, interpretable, and user-friendly to supplement clinical outcomes.…”
Section: Recommendations For Future Research Related To Measuring The...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, these systems still generate a lot of data, subject to interpretation, including multiple joint angles, and over 20-50 spatiotemporal gait metrics. 44 , 45 Thus, another avenue for future research is the development and clinical validation of gait analysis methods that can be applied to clinical settings, while being rapid, objective, intuitive, interpretable, and user-friendly to supplement clinical outcomes.…”
Section: Recommendations For Future Research Related To Measuring The...mentioning
confidence: 99%
“…However, these systems still generate a lot of data, subject to interpretation, including multiple joint angles, and over 20-50 spatiotemporal gait metrics. 44,45 Thus, another avenue for future research is the development and clinical validation of gait analysis methods that can be applied to clinical settings, while being rapid, objective, intuitive, interpretable, and user-friendly to supplement clinical outcomes. Biomechanical metrics or computational analysis have strong potential for enhancing our understanding of the biomechanical mechanism underlying rehabilitation response, because they can provide valuable insights about restitution versus compensation as well as underlying changes in motor control.…”
Section: Recommendations For Future Research Related To Measuring The...mentioning
confidence: 99%
“…To modulate gait speed from slow to a faster pace, individuals can employ various strategies, including taking longer steps, increasing step frequency, and decreasing the swing or stance phase durations, among others [14][15][16][17] . Increasing gait speed has also been associated with complex changes in joint excursions and step length asymmetry in people post-stroke [18,19] . However, previous research demonstrated that speed had little effect on joint-level coordination in injury-free adults [20,21] .…”
Section: Introductionmentioning
confidence: 99%